2018
DOI: 10.1186/s12978-018-0559-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of female gender and perspectives of pregnancy on admission in residency programs

Abstract: BackgroundMotherhood is a demanding part of any women’s life. Female interns could encounter difficulties during selection for residency program according to their plans of conceiving. Our aim is to explore the influence of female gender on the selection process of residency programs.MethodA cross sectional study was conducted in 2016 at a University Hospital in Beirut, Lebanon. Female residents and chief of departments were interviewed about the impact of the timing of motherhood during residency on the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 8 publications
(10 reference statements)
1
27
0
Order By: Relevance
“…A Japanese survey (224 respondents) found that 38% of female surgeons changed their work plans to accommodate childcare; further, acute childhood illnesses, educational activities, and parenting responsibilities affected decisions about work, and 11% had resigned their jobs . Time required for parenting also affected working hours . Two US studies reported that female surgeons undertook a greater share of childcare planning and domestic activities than male surgeons .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A Japanese survey (224 respondents) found that 38% of female surgeons changed their work plans to accommodate childcare; further, acute childhood illnesses, educational activities, and parenting responsibilities affected decisions about work, and 11% had resigned their jobs . Time required for parenting also affected working hours . Two US studies reported that female surgeons undertook a greater share of childcare planning and domestic activities than male surgeons .…”
Section: Resultsmentioning
confidence: 99%
“…The second subtheme concerned perceptions of pregnancy and motherhood, discussed in four studies from the viewpoint of the colleagues of female doctors and program directors . In three studies, conducted in the Lebanon, South Africa, and the US, doctors reported that their workloads were greater when working alongside pregnant doctors, and they rated pregnant colleagues as less productive .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations